Transformation and fate of Fe(III) in petroleum-hydrocarbon-contaminated soil and groundwater - Essouassi Elikem; David Bulmer; Kris Bradshaw; Ardalan Hayatifar; Matthew B. J. Lindsay; Steven D. Siciliano; Derek Peak (Geochemical Transactions)
Abstract In anoxic subsurface environments, low Fe(III) bioaccessibility greatly limits in situ biodegradation of petroleum hydrocarbons (PHCs). Ferric ammonium citrate is a soluble compound that has the potential to increase the bioaccessibility of Fe(III). However, in neutral to alkaline environments, Fe(III) hydrolysis can produce Fe(III) (oxyhydr)oxides that may subsequently transform or recrystallize to relatively stable and less bioaccessible phases. Accordingly, the objective of this study was to elucidate the transformation and fate of Fe(III) contributed by ferric ammonium citrate in a gasoline-contaminated subsurface environment that was undergoing in situ bioremediation. Ferric ammonium citrate, together with sodium tripolyphosphate, magnesium sulphate, and nitric acid, was continuously injected into the contaminated groundwater for about 22 weeks. Colloids in the groundwater (solid particles retained on a 0.45 $$\upmu$$ μ m filter) and soil cores were collected from the site. Fe speciation in these samples was characterized using X-ray absorption near edge structure (XANES) and Fourier transform infrared (FTIR) spectroscopy. The groundwater colloids (GWCs) contained mostly octahedrally coordinated Fe(III), but the subsoils contained both octahedrally coordinated Fe(III) and Fe(II). The fraction of Fe(II) in the subsoils generally increased after about 22 weeks of continuous amendment injection. Ferric ammonium citrate did not persist in the PHC-contaminated subsurface: the Fe(III) it contained was transformed to solid phases. Fe(III)-organic-matter (Fe(III)-OM) complex/coprecipitate and sulfate green rust were the major phases present in the GWCs; akaganeite, chloride green rust, vivianite, ferrihydrite, Fe(III)-silicate, and magnetite were present as minor phases. The subsoils contained three major phases: Fe(III)-OM complex/coprecipitate, magnetite, and calcium ferric silicate. The presence of major Fe(II) phases in the subsoils strongly indicate that secondary Fe(III) phases (especially Fe(III)-OM complex/coprecipitate) served as terminal electron acceptors during the microbial degradation of PHCs in the contaminated subsurface.